Cognitive assessment on elderly people under ambulatory care - Bruna Zortea; Daiane Porto Gautério-Abreu; Silvana Sidney Costa Santos; Bárbara Tarouco da Silva; Silomar Ilha; Vânia Dias Cruz (Universidade Federal do Ceará, 2015)
Objective: to evaluate the cognitive state of elderly people under ambulatory care and investigating the connection between such cognitive state and sociodemographic variables, health conditions, number of and adhesion to medicine. Methods: transversal, exploratory, and descriptive study, with a quantitative approach, realized with 107 elderly people under ambulatory care in a university hospital in southern Brazil, in november, 2013. The following variables were used: gender, age, civil status, income, schooling, occupation, preexisting noncommunicable diseases, number and type of prescribed medications, adhesion, mini-mental state examination score, and cognitive status. Data was analyzed through inferential and descriptive statistics. Results: the prevalence of cognitive deficit was of 42.1% and had a statistically significant connection to schooling, income, civil status, hypertension, and cardiopathy. Conclusion: nurses can intervene to avoid the increase of cognitive deficit through an assessment of the elderly person, directed to facilitative strategies to soften this deficit.